Ministério Público resolutivo no enfoque do acesso à justiça: análise teórica, instrumentos e perspectivas - Leísa Mara Silva Guimarães (2015)
For a considerable time the concern of jurists have turned to the question of how to provide the access to justice effective, in the broad sense. The recognition of group rights, the numerical crisis, slowness and inefficiency of the judiciary have driven the debate on new forms of conflict resolution, in a more complex and plural society. The resolutive public prosecution is one of the innovations with fulcrum on the effectiveness of justice in an alternative way. This dissertation focuses on the resolutive public prosecution as an institution oriented on solving conflicts related to diffuse rights, unavailable collective or individual rights, focusing on access to justice - prioritizing alternative and creative ways - for this purpose. The objective of this work is to present a theoretical study of the resolutive public prosecution based on the new approach given to this institution in the Constitution of the Republic of 1988, especially in defense of legal order, the democracy and unavailable social and individual rights. Therefore, the study in historical and evolutionary perspective of the institution was presented, from the colonial period in Brazil to the promulgation of the Republican Constitution of 1988. The new constitutional provision of the prosecution was analysed aligning it to the waves of access to justice in order to demonstrate the effectiveness of protection of group rights by prosecutors, focused on access to justice or third wave of access. Then, the instruments of extrajudicial activities as examples of resolutive action instruments were studied and prospects for consolidating the resolutive public prosecution were presented. Therefore, it was proposed the adoption of new corporate identity, humanizing action, dialogue and to be a facilitator to empower the individual and encourage democratic participation, involving complex constitutional responsibilities regarding the protection of legal order, the democratic regime and unavailable social and individual rights. Analysis of tests applied in the first stage of the competition for positions of Prosecutor of Justice of the Public Ministry of the State of Minas Gerais, Attorney of the Ministry of Labor and Prosecutor of the Federal Public Ministry for the past five years were performed, demonstrating as an example that the resolutive action for the protection of group rights is not yet prioritized institutionally with the expected intensity, given the enormous challenge that the resolutive public prosecution represents to those in charge of this public office. Accessing the judiciary only exceptionally, prioritizing work on own institutional instance, the democratic participation of society will be boosted and, at the same time, will democratize the institution, consolidating the resolutive public prosecution.